Victor Segalen, une conscience esthétique voyageuse - Adel Habbassi (Carnets)
A doctor by training, Victor Segalen had many other talents. Enlisted in the French Navy, he travelled to Polynesia and China, coming across other civilisations. The notebooks he had filled out during his journeys would provide main material for his later works. While the colonial empires laid their hands on the riches of African and Asian peoples, this poet was enamored with the diversity of the world challenged the folkloric vision of the other; he recovers the word "exoticism" and the “Exote” which he inscribes in a "diametrically opposed problematic" (Manceron, 1991: 14). "The esthetic of the diverse", exposed in his Essay on Exoticism, grants a preponderant role to the "imaginary" and in the possibilities "dream" as fundamental “aptitudes” of the « l’Exote »: A type of traveler endowed with “the power to conceive the other”. The richness in this fashion to perceive the other keeps inspiring poets, artists and philosophers throughout the world.